2014
DOI: 10.1128/aem.02577-13
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Ammonia Influences the Structure of Chemotrophic Communities in Geothermal Springs

Abstract: Source waters sampled from Perpetual Spouter hot spring (pH 7.03, 86.4°C), Yellowstone National Park, WY, have low concentrations of total ammonia, nitrite, and nitrate, suggesting nitrogen (N) limitation and/or tight coupling of N cycling processes. Dominant small-subunit rRNA sequences in Perpetual Spouter source sediments are closely affiliated with the ammonia-oxidizing archaeon "Candidatus Nitrosocaldus yellowstonii" and the putatively nitrogen-fixing (diazotrophic) bacterium Thermocrinis albus, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 40 publications
4
37
0
Order By: Relevance
“…Overall, these results confirmed that time-course changes of microbial species were associated with the changing environmental conditions49. These results are consistent with previous studies in hot springs that microbial community structure and diversity in hot springs were significantly affected by physicochemical parameters such as pH, temperature and water/sediments chemistry3491019355051525354.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, these results confirmed that time-course changes of microbial species were associated with the changing environmental conditions49. These results are consistent with previous studies in hot springs that microbial community structure and diversity in hot springs were significantly affected by physicochemical parameters such as pH, temperature and water/sediments chemistry3491019355051525354.…”
Section: Discussionsupporting
confidence: 91%
“…The high content of NO x − ‐N in region A‐3 in fall directly controls the abundance of bacteria in the taxa of Oxalobacteraceae , Pseudomonadaceae , Flavobacteriaceae , and Bacillales (Figure ) because those bacteria are involved in the transformation of NO x ‐N (Gaspar, Ferreira, Gonzalez, da Clara, & Santana, ; Choi, Lee, & Cha, ; Jung et al., ; Dodsworth, Hungate, & Hedlund, ). In summer, the average value of NH 4 + ‐N in pore water (2.4 mg L −1 ) is higher than other three seasons (Figure ), and the higher concentration of NH 4 + ‐N in pore water promotes the growth of Nitrospirales (Figure ) because the metabolism of this bacteria needs the input of NH 4 + ‐N (Hamilton et al., ), higher abundances of Nitrospirales contributed to the higher NH 4 + ‐N transformation efficiencies (Zhong et al., ). The content of TOM is more than 45 g kg −1 in winter and less than 20 g kg −1 in other three seasons (Figure ), the increase of TOM in winter directly influence the abundance of Cloacibacterium (Figure ), because these bacteria participate in organic matter degradation, and TOM provide nutrient for the growth of Cloacibacterium (Bauer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Water, biofilms, sediment, and contextual samples (soil, leaf litter, and coal) were collected as described previously [ Havig , ; Havig et al , ; Hamilton et al , ]. In short, at the time of water sampling, pH, conductivity, dissolved oxygen (DO), and temperature were measured using an Extech Instruments DO700 meter (Extech Instruments Corporation, Nashua, NH, USA).…”
Section: Methodsmentioning
confidence: 99%